Redefining Work Practices at Tertiary Care Hospital’s Orthopaedic Department in a Developing Country During COVID-19 Pandemic - Muhammad Omer Kaleem , Muhammad Sheraz , Obaid Ur Rehman (Journal of Rawalpindi Medical College, 2021)
Corona virus infection (Covid-19) originated from Chinese city of Wuhan, Hubei in late December 2019 . While the disease is thought to be highly contagious, WHO declared it as public health emergency on 30th January 2020. Pakistan reported its first corona virus infection on 26th February 2020. Initially infection was limited to those travelling from endemic areas but on 13th March 2020, Pakistan reported its first corona virus infection from local transmission. With limited testing ability and lack of uniform national corona virus response strategy, Pakistan reported total of 38,799 confirmed corona virus cases by mid May 2020. Confirmed cases reached 905,852 on 24th May 2021. Lack of definitive guidelines for health care workers (HCWs) and poor existing hospital strategies in response to COVID-19 pandemic increased the agitation and stress level among HCWs. More than half of the doctors working in our orthopedic department suffered from COVID-19. In this COVID-19 pandemic, orthopedic community should continuously evolve taking into consideration resource optimization, social distancing, innovation and best practices to minimize COVID-19 infection among health care workers who are working day and night to combat COVID- 19 in already overburdened health care system of developing country. Adopting these recommendations will not only give a uniform policy for health care workers (HCWs) of orthopedic department working in resource limited government hospitals, where thousands of patients present daily, but also limit the COVID-19 infection among health care workers (HCWs). We hope to get the best possible outcome out of current circumstances where developing nation like ours cannot afford the luxury of PPE for every health care worker and PCR COVID-19 testing for every patient.